Design of a 183 GHz subharmonic mixer using membrane integrated GaAs Schottky diode technology - Anderberg, Martin (My University, 2018)
Future ground based and space-borne meteorological instruments require sensitive heterodyne terahertz receivers in order to study precipitation and atmospheric temperature. Meteorological research is dependent on accurate water vapour measurements, typically performed with receivers at 183.3 GHz. These receivers require low noise mixers in order to meet the sensitivity requirement. At frequencies below approximately 400 GHz conventional mixers use flip-chip soldered discrete Schottky diodes. The flip-chip technique is unreliable and typically prohibits post-mount visual inspection of the diode anode, which is an important qualification step for space applications. Moreover, mechanical stresses introduced during the mixer circuit assembly can degrade the reliability. To overcome these problems a beamlead GaAs Schottky diode 183 GHz subharmonic mixer, implemented with a microstrip circuit topology, has been designed. The beamlead diode enables full visual inspection and the robust mounting of the microstrip circuit minimises the mechanical stress. Simulations showed a minimum conversion loss of 6.2 dB including conductor losses at a local oscillator frequency of 91 GHz and a power level of 2.5 dBm. The RF bandwidth was 15 % with a centre frequency of 183 GHz and the LO bandwidth was 6 % with a centre frequency of 91 GHz. The mixer was integrated with an IF LNA and measurements showed a state-of-the-art minimum receiver and mixer DSB noise temperature of 550 K and 400 K respectively at 1.6 mW of LO power which was in good agreement with the simulations.
Keywords: Elektronik; Elektrofysik; Innovation och entreprenörskap (nyttiggörande); Övrig elektroteknik, elektronik och fotonik; Informations- och kommunikationsteknik; Electronics; Electrophysics; Innovation & Entrepreneurship; Other electrical engineering, electronics and photonics; Information & Communication Technology